2001
DOI: 10.2525/ecb1963.39.103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Supply and Light Intensity on the Growth of Spring Wheat.

Abstract: The effects of water supply and light intensity on the growth of spring wheat (Triticum aestivum L.) was studied under carefully controlled conditions. The leaf water potential (LWP) was measured from 5 to 40 d after the initiation of water supply treatments (DAIT). The LWP decreased as DAIT progressed. At higher photosynthetic photon flux densities (PPFDs), the LWP decreased as the water supply decreased. The water supply rate had little impact on tiller initiation and survival under low PPFD. As the PPFD inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A similar reduction in root length of 43% was shown for castor bean plants ( Penfound, 1932 ). For wheat plants, Tamaki et al (2001) reported an inhibition of 68% in root biomass under combined low light and low water availability. The difference in reduction on wheat plants could be ascribed to the discrepancy in time points when plants were measured or harvested.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A similar reduction in root length of 43% was shown for castor bean plants ( Penfound, 1932 ). For wheat plants, Tamaki et al (2001) reported an inhibition of 68% in root biomass under combined low light and low water availability. The difference in reduction on wheat plants could be ascribed to the discrepancy in time points when plants were measured or harvested.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in reduction on wheat plants could be ascribed to the discrepancy in time points when plants were measured or harvested. Tamaki et al (2001) harvested the plants at anthesis whereas the plants in this study were grown for only 3 weeks in rhizoboxes (because roots reached the bottom of the rhizoboxes 3 weeks after sowing and measurements were stopped). During these 3 weeks, inhibition of root extension increased from 23% to 42% and it may have increased more over plant development up to 68% at anthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S1a and b). This may be because plant growth is influenced by various conditions, including light intensity, light spectrum, temperature, and CO 2 concentration [13,17,[21][22][23]. Bhatta et al [13] reported that higher plant height and GN were observed in a glasshouse than in a speed-breeding room, although this was the result of delayed DTH in a glasshouse with a natural photoperiod.…”
Section: Glasshouse With Minimized Artificial Control Enables Speed B...mentioning
confidence: 99%